A critical study of Anti-Corruption Law in India with a special reference to Anti-Corruption Bureau, Faridabad - Himaz Matta, Anjali Dixit (Journal of Neonatal Surgery, 2025)
This study critically examines the framework of anti-corruption law in India, with a special focus on the functioning of the Anti-Corruption Bureau (ACB), Faridabad. It explores the historical evolution of anti-corruption statutes including the Prevention of Corruption Act, 1988; the Lokpal and Lokayuktas Act, 2013; and related institutional mechanisms such as the Central Vigilance Commission and the Whistle Blowers Protection Act. By analyzing real-world case studies from Faridabad, the research assesses the effectiveness of the ACB in handling corruption-related cases. Through a literature-informed lens, it addresses the limitations of existing strategies such as delays in prosecution, political interference, and resource constraints. The paper also incorporates theoretical insights on systemic corruption, digital tools, educational outreach, and public engagement. Findings suggest that legal frameworks, while robust on paper, require stronger institutional independence and public participation to be effective. The study recommends structural reforms and multi-institutional collaboration to improve anti-corruption enforcement at the grassroots level.